Intracranial Meningioma Aggressivity Image and Level of Malignancy in Head Magnetic Resonance Imaging (MRI). (Medico Legal Update, 2020)
Background: Meningioma is the second most common central nervous system neoplasm in adults, usually benign that originally from arachnoid cap cells. Meningioma is categorized by WHO classification as benign (grade I), atypical (grade II), and anaplastic (grade III). Objectives: This study to know strong correlation between the image of intracranial meningioma aggressiveness and malignancy. Method: Restrivectively, forty-intracranial meningiomas of new cases who had undergone surgery from January 2014 to June 2015, preoperative MRI head examination and Anatomy Pathology at Dr. Soetomo Surabaya, observed signs of aggressiveness of meningioma and malignancy rate that analyzed by contingency coefficient and Spearman correlation coefficient. Results: Based on age 30-65 years; 82.5% of women and 17.5% of men was got a strong correlation between bone destruction (C = 0.533); weak association of intratumoral cystic changes (C = 0.230), hyperostosis (C = 0.327), vascular encasement (C = 0.327); a very weak correlation of extracranial tumor extension (C = 0.139), cerebral peritoneal edema (C = 0.104); with a malignant degree in meningioma. Conclusion: There was a strong correlation between bone destruction and malignancy rates in meningioma.